Role of Sincerity and Patience in Helping Attitude of Psychology Department Students in North Jakarta - Hasan, Aliah B. Purwakania (Faculty of Psychology, Universitas Surabaya, 2010)
The purpose of this research was to describe role of sincerity and patience toward helping attitude of psychology department university students in North Jakarta. This survey used Likert type scale (seven scales) as research instruments, and calibrated with rating scale model. This research’ results, processed with correlation technique, showed correlation be- tween sincerity and patience, between sincerity and helping attitude, and between patience and helping attitute. However, advance data processing with structural equation model showed weak role of sincerity toward helping attitude and only had standardized undirect effect. In this model, patience appeared as mediator variabel between sincerity and helping attitude. Sincerity played specific role as determinant of patience, and patience as determi- nant of helping attitude. The results showed uniqueness of the eastern world in helping be- havior that is not only based on reinforcement system. Tujuan penelitian ini adalah menjelaskan ketulusan dan kesabaran terhadap sikap menolong para mahasiswa psikologi di Jakarta Utara. Survei ini memakai skala tipe Likert (tujuh skala) sebagai instrumen penelitian, dan dikalibrasi dengan model skala rating. Hasil penelitian ini, diproses dengan teknik korelasi, menunjukkan korelasi antara ketulusan dan kesabaran, antara ketulusan dan sikap menolong, dan antara kesabaran dan sikap menolong. Namun, pengolahan data lanjut dengan model persamaan struktural menunjukkan peran lemah ketulusan terhadap sikap menolong dan hanya memiliki efek tak-langsung yang standar. Dalam model ini, kesabaran muncul sebagai variabel mediator antara ketulusan dan sikap menolong. Ketulusan memainkan peran spesifik sebagai penentu kesabaran, dan kesabaran sebagai penentu sikap menolong. Hasilnya menunjukkan keunikan Dunia Timur dalam perilaku menolong, yang tak hanya didasarkan pada sistem penguat.